MATHEMATICS LEARNING INSTRUMENT DEVELOPMENT BASED ON RME ASSISTED BY LIVE WORKSHEET TO DEVELOP PROBLEM SOLVING SKILLS - Faricha, Nia Agustina; Kurniawan, Agus Prasetyo; Yanti, Aning Wida; Prayitno, Lydia Lia (IAIN Ambon, 2024)
Learning mathematics experiences several problems, one of them is problems related to problem solving skills, the researchers applied the RME approach that presented a real-world context so that students could construct their own understanding with the help of live worksheets as an assisted media for mathematics learning. The existence of an approach that is applied using developing technology is expected to have trained students to solve problems properly and correctly. This study to develop learning tools that can develop mathematical problem solving skills with realistic mathematics education (RME) approach assisted by live worksheet application. This type is a Research and Development (R&D) with the ADDIE model (analysis, design, development, implementation and evaluation). This research was applied to 8th-A grade students at SMPN 1 Baureno Bojonegoro as many as 32 students. Data were collected using several techniques, field notes, validation, and tests. The results of data analysis showed that based on the indicators determined by researchers, the learning device was declared